Genomic Alterations Found in Recurrent Uterine Sarcomas of African-American Women [18A]. (May 2018) - Geisler, John; Manahan, Kelly; Webb, Kathryn; Bryant, Allison; Moore, Crystal
Abstract : INTRODUCTION: To describe the frequency of genomic alterations found in tumors from a population of African-American women with recurrent uterine sarcomas METHODS: Medical records were analyzed for all African American women with recurrent uterine sarcomas who underwent next generation sequencing of their tumors. Demographics were collected as well as all tumor genomic alterations. Data was evaluated by SPSS to see if any consistent genomic alterations were found. RESULTS: Twenty-four African-American women had next-generation sequencing on their recurrent uterine sarcomas with 12 having high-grade leiomyosarcomas (LMS), 11 having carcinosarcomas (MMMT), and one having an undifferentiated uterine sarcoma. The mean age of the patients was 54 years (median 52 years, 95%CI 51.2-57.7). The mean mutation burden/Mb was 6.4 mutations/Mb (median 4.5, 95%CI 1.7-11.1). Nineteen tumors had 1-5 mutations/Mb, 4 had 6-10 mutations/Mb and 1 had >10 mutations/Mb. p53 mutations occurred in the majority of tumors (LMS 66.7%, MMMT 63.6%; respectively). The gene with the second most alterations was PIK3CA (LMS 8.3%, MMMT 45.5%). BRCA2 mutations were the only other genomic alterations to occur in >10% of recurrent uterine sarcomas (LMS 16.7%, MMMT 27.3%). CONCLUSION: In this population of African-American women with recurrent uterine sarcomas, the 3 genes found to most commonly harbor genomic alterations were p53, PIK3CA, and BRCA2.